The effectiveness of an instructional design according to the participatory thinking strategy in the achievement and practical skills of the teaching aids laboratory and the attitude towards the material (Journal of the College of Basic Education, 2022)
The current research aims to know the effectiveness of educational design according to the participatory thinking strategy in the achievement and practical skills of the teaching aids laboratory and the attitude towards the material. In order to achieve the goal of the research, the null hypotheses were formulated and an experiment was conducted that lasted a full semester, which is the first semester. The research community consisted of fourth-stage students in the Department of Physics from the College of Education at Al-Mustansiriya University for the academic year (2012-2013). The research sample was deliberately chosen, and it numbered (47) male and female students. The equivalence between the two research groups was confirmed through the variables